Thunderbolt of Anger - Kawa, Szymon (No Limits, 2023)
Poland’s abortion law is among the most restrictive in Europe. The decision to tighten it up led to the largest protests since the fall of communism in 1989. To offer a fair explanation of the so-called Women’s Strike, we first need to look back at how the abortion law in Poland changed over the years.